Penerapan Model Direct Reading Thinking Activity (DRTA ) Untuk Meningkatkan Keterampilan Membaca Pemahaman Siswa Sekolah Dasar - Tria Nurul Hidayah; Yenni Fitra Surya; Putri Hana Pebriana; Yanti Yandri Kusuma; Rizki Ananda (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
This study aims to determine the improvement of students' reading comprehension skills on the theme of the beauty of togetherness through the application of the Direct Reading Thinking Activity (DRTA) model for the fourth grade of the State Elementary School 011 Pulau Jambu. The subjects in this study were 1 teacher and 24 fourth grade students at SDN 011 Pulau Jambu. Data collection techniques using observation techniques, tests, and documentation. Can be seen from before the act of students learning completeness of 29,17% was in the less category with an average 60,21. In the first cycle, it increased to 54,17% in the sufficient category with an average of 67,81. Then in the second cycle, it increased to 83,33% in the very good category with an average 86,46 .Thus, it can be concluded that the Direct Reading Thinking Activity (DRTA) learning model can improve students' reading comprehension skills on the theme of the beauty of togetherness in class IV at SDN 011 Pulau Jambu.